A Review of Biomass-Based Natural Coagulants for Water Pollution Remediation: Impact of Properties and Coagulation Operational Parameters - Nur Faizzah Husna Mohammad Ali; Megat Ahmad Kamal Megat Hanafiah; Sabiha Hanim Saleh; Mohd Tajudin Mohd Ali; Shariff Ibrahim (AUIQ Complementary Biological System)
The rapid growth of cities, industries, and population has made tackling water scarcity increasingly challenging as the global demand for clean drinking water continues to rise. Consequently, extensive research in water and wastewater treatment, specifically focusing on the coagulation process, has ensued. Coagulation plays a critical role in water treatment, and its effectiveness depends on the type of coagulant used. However, the widespread use of chemical coagulants raises concerns for the environment and public health. Consequently, there has been growing interest in exploring natural alternatives derived from plants and animals. This review examines how the properties of natural coagulants, as well as coagulation process parameters, impact their ability to remove pollutants. Factors such as surface morphology, surface charge, molecular weight, and functional groups of the coagulant, as well as coagulation parameters like pH and dosage, significantly influence the removal of turbidity, color, and organic matter from water. Effective natural coagulants typically possess rough and porous structures that help trap particles, have a higher molecular weight for better performance, exhibit a higher zeta potential for improved charge neutralization, and contain reactive functional groups. Coagulation activity is greatly affected by the pH of the water being treated and the amount of natural coagulant used. By optimizing these properties and conditions, natural coagulants derived from plants offer environmentally friendly and cost-effective alternatives to chemical coagulants in large-scale water treatment. This review distinguishes itself by providing a comparative analysis of both plant-based and animal-based natural coagulants, especially in terms of the influence of coagulant properties, addressing a gap in recent literature that predominantly focuses on coagulation operational parameters.